Identification of evolutionarily conserved amino acid residues in homeodomain of KNOX proteins for intercellular trafficking - Chen, Huan (Landes Bioscience, 2014)
Maize KNOTTED (KN1) homeodomain (HD) protein is a well-known mobile transcription factor crucial for stem cell maintenance. Recent studies have revealed that the trihelical HD of KNOTTED1-like homeobox (KNOX) proteins is necessary and sufficient for selective cell-to-cell trafficking. Also, the efficient trafficking ability for HD is likely to be acquired during the evolution of early nonvascular land plants. Here, using the point-mutated HD of KN1 and SHOOT MERISTEMLESS (STM) in the trichome rescue system, together with molecular structure modeling, we have found the evolutionarily conserved amino acid residues, such as arginine in helix α1 and leucine in helix α3, which are essential for intercellular trafficking. Our studies provided important clues for the 3-dimensional protein structure required for cell-to-cell movement of non-cell-autonomous transcription factors.